Market discipline in financial regulation - Flannery, Mark (Henry Stewart Talks, 2009)
Governments bear some of the risk taken by financial institutions: formally (as in deposit insurance) or informally (as in support provided during a crisis), Much of the financial system's regulatory oversight is best viewed as an effort to control this indirect source of risk to the government and its taxpayers, Traditional supervision relies on inspections by government personnel, who tend to focus on accounting outcomes, Market investors also evaluate financial firms' activities, The resulting market prices (of equity, bonds, deposits, etc.) can supplement the government's traditional supervisory techniques, at least under certain circumstances